Regulamin uroczystości złożenia hołdu lennego JKM Fryderykowi Wilhelmowi, królowi pruskiemu, przez suwerenne Księstwo Śląskie i Hrabstwo Kłodzkie dnia 15 października 1786 r. = Instructions for the ceremony of swearing fealty to his majesty Frederic Wilhelm, king of Prussia, by the Sovereign Duchy of Silesia and the County of Kłodzko, held on october 15th, 1786 - Konopnicka, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The set of instructions for the ceremony of swearing fealty in 1786, included in the collection of decrees, edicts and mandates for Silesia - issued by the monarchs from 1740 - was one of the first orders by Frederic Wilhelm II, successor to Silesia's annexation's author, Frederic the Great.
Keywords: Prusy - polityka - historia - 18 w.; Księstwo Śląskie; Hrabstwo Kłodzkie; hołd lenny; Fryderyk Wilhelm II Pruski (król pruski; 1744-1797)